Raman spectroscopy of single nanoparticles in a double-nanohole optical tweezer system. (22nd September 2015) - Jones, Steven; Al Balushi, Ahmed A; Gordon, Reuven
Abstract: A double nanohole in a metal film was used to trap nanoparticles (20 nm diameter) and simultaneously record their Raman spectrum using the trapping laser as the excitation source. This allowed for the identification of characteristic Stokes lines for titania and polystyrene nanoparticles, showing the capability for material identification of nanoparticles once trapped. Increased Raman signal was observed for the trapping of multiple nanoparticles. This system combines the benefits of nanoparticle isolation and manipulation with unique identification.